Drugs, Icelandic society and new policy measures - Gunnlaugsson, Helgi (Stjórnsýslustofnun, 2013)
The drug problem is believed by many to be one of the most serious social problems in western societies. Public attitude surveys show that most believe drug use to be the most serious crime problem in Iceland and alcohol and drug use the most important cause why some people end up in crime. Cannabis use, the most frequent drug, has regularly been measured among students but studies among adults have been examined to a lesser extent. As a result, not much is known about how consumption starting among youth develops into adulthood, if it increases, stays the same or decreases. Furthermore, not much is known about social characteristics of those who abuse hard drugs in Icelandic society. In this article, cannabis use among adults in Iceland is examined. How many have ever tried cannabis during their lifetime, how many have used it more than ten times, and how many during the last six months before the survey took place? The position of injecting drug users is examined and what risk factors are associated with this use. Public perceptions of which crime type is most serious in society and why some people commit crimes is explored. The main findings show that the number of those who have ever used cannabis in Iceland has increased in the past few years but regular use of cannabis among adults is insignificant. Those who use hard drugs are in a weak social position and face various problems. A social policy sensitive to different levels of drug use in society is urgent in addition to strengthening social and health care measures to tackle the problem of hard drug users in society. Fíkniefnavandinn er af mörgum álitinn einn helsti vandi sem vestræn ríki glíma við í dag. Viðhorfsmælingar á Íslandi sýna að flestir telja neyslu fíkniefna alvarlegasta vandamál afbrota en samneyslu áfengis og fíkniefna mikilvægustu ástæðu þess að sumir leiðast út í afbrot. Neysla algengasta fíkniefnisins, kannabis, hefur reglulega verið mæld meðal grunnskólabarna hér á landi en neysla fullorðinna hefur minna verið könnuð. Lítið er því ...